Effect of fuel additives on agricultural straw pellet quality - Emami, Shahram; Tabil, Lope G.; Adapa, Phani; George, Elizabeth; Tilay, Ashwini; Dalai, Ajay; Drisdelle, Mark; Ketabi, Lily (International Journal of Agricultural and Biological Engineering, 2014)
An investigation was conducted to determine the effect of addition of different levels of AK2, a fuel additive that reduces ash fusion for agricultural biomass, on the physico-chemical properties of biomass pellets. Three different biomass straws, barley, oat, and wheat were ground at two hammer mill screen sizes of 0.8 mm and 1.6 mm. Each ground biomass sample was mixed with three levels of AK2, 0.05%, 0.10%, and 0.15% by mass and also a blank (no AK2) was set aside for comparison. Pellets were made using single-pelleting unit at a pre-set load of 4 400 N corresponding to a pressure of 138.9 MPa. Physical quality of pellets were determined by measuring pellet density, relaxed density, durability, and the specific energy required to make a pellet. Pellets having higher durability values (74%-88%) were obtained from ground straw at hammer screen size of 0.8 mm and AK2 level of 0.15% compared to other treatments. Carbon, hydrogen, nitrogen, and sulfur content of blank pellets and those with 0.15% AK2 at hammer screen size of 0.8 mm were determined. Pellets made with 0.15% AK2 at hammer screen size of 0.8 mm, manufactured by pilot-scale pellet mill, were gasified and the tar content was determined. The tar content of pellets with 0.15% AK2 was significantly lower than blank pellets. Keywords: biomass, biofuels, slag, foul, pelleting, fuel additive DOI: 10.3965/j.ijabe.20140702.011 Citation: Emami S, Tabil L G, Adapa P, George E, Tilay A, Dalai A, et al. Effect of fuel additives on agricultural straw pellet quality. Int J Agric & Biol Eng, 2014; 7(2): 92－100.